2022
DOI: 10.1371/journal.pcbi.1010318
|View full text |Cite
|
Sign up to set email alerts
|

Suprathreshold perceptual decisions constrain models of confidence

Abstract: Perceptual confidence is an important internal signal about the certainty of our decisions and there is a substantial debate on how it is computed. We highlight three confidence metric types from the literature: observers either use 1) the full probability distribution to compute probability correct (Probability metrics), 2) point estimates from the perceptual decision process to estimate uncertainty (Evidence-Strength metrics), or 3) heuristic confidence from stimulus-based cues to uncertainty (Heuristic metr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 72 publications
5
36
1
Order By: Relevance
“…The poor performance of the unscaled evidence strength class suggests that in mixed difficulty designs, observers modulate their confidence by the amount of sensory uncertainty in their internal representation of the stimulus in both the visual and auditory domain. The role of sensory uncertainty in adjusting response criteria has been demonstrated previously in the visual modality Denison et al, 2018;Locke et al, 2022;Qamar et al, 2013) but has not been demonstrated in the auditory modality. In addition to providing evidence that observers take sensory uncertainty into account across modalities, our study also provides insight into the extent to which these processes are consistent with Bayesian or non-Bayesian accounts of confidence.…”
Section: The Importance Of Accounting For Sensory Uncertaintymentioning
confidence: 93%
See 1 more Smart Citation
“…The poor performance of the unscaled evidence strength class suggests that in mixed difficulty designs, observers modulate their confidence by the amount of sensory uncertainty in their internal representation of the stimulus in both the visual and auditory domain. The role of sensory uncertainty in adjusting response criteria has been demonstrated previously in the visual modality Denison et al, 2018;Locke et al, 2022;Qamar et al, 2013) but has not been demonstrated in the auditory modality. In addition to providing evidence that observers take sensory uncertainty into account across modalities, our study also provides insight into the extent to which these processes are consistent with Bayesian or non-Bayesian accounts of confidence.…”
Section: The Importance Of Accounting For Sensory Uncertaintymentioning
confidence: 93%
“…), which is unbounded and allows for greater differences in confidence at different levels of sensory uncertainty (see bottom panel of Fig 1E ; Adler Locke et al, 2022).…”
Section: Bayesian Modelsmentioning
confidence: 99%
“…Such arbitration studies do exist, but they are relatively few (see e.g. (Adler & Ma, 2018b;Locke et al, 2022;Peters, Fesi, et al, 2017;Peters, Thesen, et al, 2017)). If we want to identify which model is (more) correct, we must design our stimuli and experiments specifically with such arbitration in mind.…”
Section: Current State Of the Fieldmentioning
confidence: 99%
“…Having different best-fitting models across participants is a common phenomenon in cue combination and multi-sensory research (e.g., 76,77), as well as perceptual confidence (35,46).…”
Section: Performance Strategiesmentioning
confidence: 99%
“…In order to incorporate a confidence judgment into a naturalistic reaching task more complex models need to be used. Bayesian approaches to confidence have gained popularity for handling non-binary decisions among other tasks, describing confidence as the posterior probability of being correct given the presence of noise (13,(29)(30)(31)(32)(33)(34)(35). Sensorimotor confidence is positioned uniquely to benefit from the Bayesian approach given that measurements in motor tasks are effector specific and recorded in a way that captures the noise naturally present in the system.…”
mentioning
confidence: 99%